Modulating effect of cotyledon cell microstructure on in vitro digestion of starch in legumes. (November 2019) - Do, Duc Toan; Singh, Jaspreet; Oey, Indrawati; Singh, Harjinder
Abstract: The cotyledon of legumes consists primarily of numerous starch granule-containing cells bound together by the pectin-rich middle lamella. In this study, we provided detailed characterisation of the microstructure, physicochemical properties, and in vitro starch digestion of cotyledon cells. Raw, intact cells were obtained from adzuki bean, chickpea, lentil, and lima bean using a sequential acid-alkali isolation method. These cells were then cooked and subjected to in vitro gastric and small intestinal digestion. Light micrographs of the cells showed various cell shape (ellipsoid or spherical) and size (mean diameter, D50 ∼98–118 μm). The cells contained tightly packed starch granules (D50 ∼19–40 μm) that were embedded in protein matrix in the cytoplasm and enclosed within intact cell walls. Upon heating in excess water, starches inside cells exhibited considerably lower swelling, solubility, and paste viscosity, as well as higher gelatinisation transition temperatures than isolated starches. After cooking under similar conditions, starches inside cells exhibited significantly lower rate and extent of hydrolysis than isolated starches during subsequent in vitro digestion. Scanning electron microscopic study of representative cells showed the preservation of cell wall intactness throughout cooking and digestion. The results indicate that the cotyledon cell structure restricts starch gelatinisation and impedes accessibility of amylolytic enzymes to intracellular starch, thus limiting the rate and extent of starch digestion in vitro . Graphical abstract: Image 1 Highlights: Starch granules are encapsulated by protein matrices and cell walls of cotyledon cells. Swelling and gelatinisation of starch inside cells were restricted during cooking. Cell walls remained predominantly intact throughout cooking and enzymatic digestion. Alpha-amylases had limited access to intracellular starch. Cotyledon cell microstructure limits in vitro digestion of starch in legumes.